Shakespeare's domestic economies : gender and property in early modern England - Korda, Natasha (University of Pennsylvania Press, 2002)
A significant contribution to Shakespeare criticism that integrates feminism, materialist criticism, and legal history to offer an original look at how women's management of household goods became an important site of female struggle and resistance to England's patrilineal property regime. "Korda draws on the best aspects of a variety of recent critical approaches while charting new territory of her own."--Choice
Keywords: Shakespeare, William, -- 1564-1616 -- Views on sex role.; Shakespeare, William, -- 1564-1616 -- Characters -- Women.; Shakespeare, William, -- 1564-1616 -- Views on property.; Shakespeare, William, -- 1564-1616; House furnishings in literature.; Housekeeping in literature.; Property in literature.; Sex role in literature.; Women in literature.; Ameublement dans la littérature.; Travail domestique dans la littérature.; Rôle selon le sexe dans la littérature.; Femmes dans la littérature.; LITERARY CRITICISM -- Shakespeare.; House furnishings in literature; Housekeeping in literature; Property; Property in literature; Sex role; Sex role in literature; Women in literature; Cultural Studies.; Gender Studies.; Literature.; Medieval and Renaissance Studies.; Women's Studies.; Electronic book.